Indonesian Women's Right to Gender Equality and Sexual Reproductive Health; a Human Right Perspective - Pratama, Obi (Fakultas Hukum Universitas Primagraha, 2023)
In a legal and social context, the reproduction right is a problem of power relations and society, particularly laws. Women usually remain silent since they lack power. Not because of their personalities, but due to the influence of politics, economics, and society. Their interactions with men, their families, their friends, and society are all crucial. Gender-based laws are the result of communal attitudes toward women, gender, and sex. This results in a variety of forms of violence during implementation. The study adopts a description-based approach, and the analysis of how norms are applied to positive laws is the main research objective. Normative juridical research is well-versed in this approach. In order to develop the idea of gender equity, the study examines how human rights are applied and whether they are acceptable for women's reproductive rights based on gender. Additionally, the statuary approach, conceptual approach, and comparative technique are used in this type of research. These methods are used to identify problems and possible solutions. The results of the study indicate that when it comes to the safety or health of their reproductive systems, women have a special right to protection at work and in their professions Gender inequality is a cause of violations of women's human rights. Gender discrimination and violence against women in Indonesia are still pervasive.